(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
In an era marked by hybrid threats, rapid technological advancement, and increasingly complex battlefields, the effectiveness of the Malaysian Armed Forces (MAF) hinges on the preparedness of its military personnel to evolve into Smart Soldiers. This article highlights the pivotal role of Professional Military Education (PME) in developing military personnel who are capable of operating across diverse operational domains. By focusing on the individual development of military personnel, the article identifies key areas of study that examine how PME enhances critical competencies such as decision-making, leadership, adaptability, and strategic thinking, ultimately equipping them to meet both contemporary and future operational challenges